Pengembangan Kapasitas Aparatur Pemerintah Desa dalam Rangka Mewujudkan Good Governance - Fajarwati, Neri (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2019)
The existence of the village government lately has not been able to function properly. One factor is that the capacity of the village apparatus is inadequate and the skills possessed are still very limited. Minimal education and training to improve the ability of village officials is the root of the problem. This study uses descriptive qualitative methods and the approach used in this study is a qualitative approach. The purpose of writing this article is to find out the things, efforts and constraints of developing the capacity of the current village apparatus. The problem of limited budget is an obstacle in improving the quality of village officials. The lack of a budget has had an effect on programs and activities in the context of developing the capacity of village apparatus that cannot be realized. The steps that can be used are, capacity building through training for orderly village administration, manuscripts and management of official letters, village government accountability reports, Compilation of Village Expenditure Budget, Village Fund Allocation Management and Village Wealth Management and Management of Village Owned Enterprises. The need for cooperation and attention between the Central Government and the Regional Government to conduct training on an ongoing basis, especially in the village of Cibodas